BIOSURVEY OF HEAVY METALS MERCURY (HG), LEAD (PB), AND CADMIUM (CD) IN JAKARTA BAY AFFECTED BY RECLAMATION - Salman, Salmita
Man-made islands allegedly alter the coastline that slowing pollutants retention time. Green mussels (Perna viridis L.) are one of the organisms known to accumulate heavy metals. Biosurvey is a scientific study about organisms to assess ecological conditions need to be conducted to acquaire information on heavy metal content in man-made habitats and biota. The aims of this research are (1) to identify the water quality related to heavy metal presence; (2) to measuring heavy metal content in green mussells (Perna viridis L.) around the reclaimed island; (3) to determining heavy metal level pollution on the reclamation island. Sampling was conducted in August 2017 in reclamation islands C and D. Heavy metal measurements values refer to the SNI method 3554-2015, total suspended solids (SNI 06-6989.3-2004), biological oxygen demands (BOD) (SNI 6989.72-2009) and chemical oxygen demands (COD) (SNI 6989.73-2009). Data were analyzed descriptive quantitatively to the waters physics-chemical parameters and heavy metal content in green mussells. The results show biological oxygen demands (BOD) 265,3-593,2 mg/L and chemical oxygen demand (COD) 70,0-85,1 mg/L has exceeded the water quality standard (20 mg/L) which indicate high level of pollution. The results of heavy metals examination in seawater show that mercury (Hg), cadmium (Cd), and lead (Pb) are below the tools detection limit (<0.0002; <0.00011; <0.00086 mg/L) and below Sea Water Quality Standard for Biota based on the Decree of the Minister of Environment Number 51 in 2004. Concentrations of heavy metals mercury, cadmium and lead in sediments around the reclaimed islands area are below heavy metal standards for sediments based on IADC / CEDA in 1997. Mercury (Hg) levels below the tools detection limit (<0.0004 mg/L); cadmium (Cd) ranges from 0.02-0.20 mg/L; lead (Pb) ranges from 0.50 to 5.46 mg/L. In general, water and sediments around reclaimed islands are not polluted by heavy metals so they do not endanger the biota. Cadmium and lead concentrations in the sediments is higher than in the water, one of the reason is because the sediment has lower pH (5.7-6.7) than water (8.4-8,9) which would trigger higher adsorption of heavy metals in sediments. Heavy metals exanimation in green mussels indicate that mercury (Hg), cadmium (Cd), and lead (Pb) are below the tools detection limit (<0.001; <0.00011; <0.00086 mg/L) and below the heavy metal quality standard on bivalves based on SNI 7387-2009. One of the factors that affect heavy metals concentrations in green mussels below the device detection limit is the low concentrations of heavy metals in water and sediments. Heavy metals quality in water, sediment and mussels are below the standard quality and based on the STORET method belong to grade A. The heavy metal index on reclaimed island is 18 and considered good. Based on the results obtained, it can be concluded that the reclaimed islands C and D environment in August 2017 were safe from heavy metal mercury, cadmium, and lead pollutions.